Experimental Study on a New Reinforcement Method for Multilayer Industrial Building’s Vibration - Kaizhong Xie; Hongwei Wang; Jianxi Zhou; Xiao Luo; Miao Yue (Advances in Civil Engineering)
In order to study a new reinforcement method for multilayer (4 layers) industrial building’s vibration, firstly, a new reinforcement method using a short-pier shear wall was put forward. Secondly, an engineering example of a multilayer industrial building with abnormal vibration was introduced. A three-dimensional finite element model of multilayer industrial building was established, and field vibration test was carried out. Test results showed that abnormal vibration of industrial building was caused by resonance between machines and multilayer industrial building. Finally, multilayer industrial building was reinforced by a new reinforcement method, and vibration experiment was carried out after reinforcement. The results show that the new reinforcement method has a good reinforcement effect. Strength and stiffness of multilayer industrial building were obviously improved, and natural frequency of industrial building in the length direction increased from 2.45 Hz to 5.87 Hz, natural frequency of industrial building in the width direction increased from 2.94 Hz to 7.83 Hz, frequencies of machines and frequencies of multilayer industrial building were not in resonance range, acceleration and velocity vibration characteristics of multilayer industrial building were improved, which can provide reference for the reinforcement of multilayer industrial building with a similar structural configuration.